Modern Lighting is a Guarantee of Production Safety - A. X., Rasulev; N. U., Baymuratova (European Journal of Life Safety and Stability (2660-9630), 2022)
Today light diode to modules use for under light of the buildings, cars, streets and advertising design, fountains, subways and bridge. Given illumination use for under light production and office premiseses, home interior and furniture. Reliability light diode sources of the light allows to use them in it is difficult available for frequent change places (the built-in ceiling illumination, inwardly adjuster ceiling and t. d.).